Propuesta de mejora de la rotación de inventarios de bobinas de acero en la empresa Aceros Procesados S.A. basados en la implementación del Business Process Management (BPM) - Buse Visconti, Rollin Alfredo (2022)
Aceros Procesados S.A. is a company dedicated to the manufacture and commercialization of steel decks located in the city of Lima. Based on the company's need to improve the purchasing process, this research study is carried out to determine the problem and the main causes for the detected problem: low inventory rotation with a result of 0,8714 per year. Likewise, an improvement in the purchasing process is proposed to solve the problem found. In the development of this work, the technical, economic, and social feasibility of implementing an improvement is demonstrated, which directly impacts the results of the company. As part of the evidenced problem, the three main causes that originate this problem were identified: inefficient purchase process, intuitive purchases, and a non-existent demand plan. Based on this, the solution proposes the automation of the purchasing process through a Business Process Management (BPM) platform, a redesign of the purchasing process and the implementation of demand management. In the other hand, the minimum level of stock that each product needs were determined, based on historical demand. In this sense, savings and efficiencies are generated by avoiding having an overstock over costs. The solution will be successful to the extent that it can have a correct demand planning and a more efficient and automated process. The project horizon is 12 months, and the project investment amounts to a total of S/ 76 000 soles. The solution would be implemented through its own financing, for which only an economic evaluation is considered. The result is an IRR of 22% and a NPV of S/ 36 921.